Formulation and Optimization of Omeprezole Floating Tablet by Wet Granulation Technique - Kaushal, Sahil; Dev, Dhruv; Prasad, D.N; Sharma, Rajni (Journal of Drug Delivery and Therapeutics, 2019)
Omaprezole is a proton pump inhibitor, antacid drug. It is categorized as class II in BCS system of classification of drugs. Omaprazole inhibits the H(+)-K(-) ATPase in the proton pump of gastric parietal cells and highly effective inhibitor of gastric acid secretion. Floating tablet is nowadays considered as one of the best method to enhance the retention time of tablet in stomach. To get a better dissolution rate, the retention time of Omaprazole is enhanced by the floating technique. The aim of the work is to formulate the floating tablet of Omaprazole and evaluation of tablets invitro performance. The floating tablets are prepared by using two different polymers; HPMC K15, HPMC K100. Wet granulation method was used to prepare tablet. The polymers added in different ratios. The increasing concentration of polymers is responsible for enhancement of drug content and percent yield due to increase in the swallability of polymer.Invitro drug release study was performed using United State Pharmacopoeia (USP) type II dissolution test apparatus employing paddle stirrer at 50 rpm using 900ml of 0.1 N HCL buffer maintained at 37⁰C±0.5⁰C as the dissolution medium. The FTIR, DSC studies of Omaprazole floating tablet indicated the phase inversion of Omaprazole from crystalline to amorphous form. The F3 formulation show increased drug release as compare to pure drug in 24 hrs. It can be concluded that the floating tablet of Omaprazole prepared with mixture of HPMC K15 and HPMC K100 has greater retention time than pure drug and marketed formulation. Keywords-   Omaprezole, Gastroretentive floating tablet, HPMC K15, HPMC K100